Knowledge Management as an Enabler of Change and Innovation in Africa - Ahmed, A.; Ghoneim, S.; Kim, R. (2012)
In recent years, mainstreaming knowledge management practices in government processes has assumed increasing importance. How have governments in Africa, if at all, incorporated knowledge management in governance and how inclusive has this process been? This paper will attempt to answer these key questions by examining the experiences and lessons learned in efforts to build knowledge management capacity across Africa. In doing so, the paper will provide a summary of the key presentations of the latest two-day conference. Knowledge Management as an Enabler of Change and Innovation in Africa (Cairo, 2007). Central to discussions was the need to create an enabling environment encouraging the adoption of knowledge management practices in Africa and the utilisation of indigenous knowledge assets as an important input in poverty alleviation strategies. More importantly, the paper outlines the challenges that can be observed and what opportunities for building the Africa Knowledge System are available. Finally, the paper concludes with a discussion of strategic and policy implications of these finding for achieving sustainable development in Africa.